Preschool teachers' self-efficacy, burnout, and stress in online professional development: a mixed methods approach to understand change. Issue 3 (2nd July 2020) - Roberts, Amy M.; LoCasale-Crouch, Jennifer; Hamre, Bridget K.; Jamil, Faiza M.
ABSTRACT: This mixed methods study examines the impact of online professional development on preschool teachers' self-efficacy, burnout, and stress. Participating teachers (n = 89) were randomly assigned into four groups: one of three treatment conditions (course-only, conference, reflective writing) or a control group. All treatment conditions received a 14-week online course on teacher-child interactions, which included regular homework assignments and community discussion boards. The conference and reflective writing conditions received additional supports. Regression analyses revealed that teachers who were in the course-only treatment condition had decreased self-efficacy and increased emotional exhaustion, a component of burnout, relative to the control group. However, teachers in the conference and reflective writing conditions did not experience such negative effects. Qualitative analyses suggest that all teachers tended to focus on personal challenges within the course, but teachers who had access to conference and reflective writing supports benefited from the availability of emotional outlets and/or opportunities for feedback